2021
DOI: 10.1021/acs.joc.0c03069
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Impossible Rings in Macrocyclooligomerizations for Cyclodepsipeptide Synthesis: The 18-from-12 Paradox

Abstract: A reinvestigation into the macrocyclooligomerization (MCO) of a tetradepsipeptide is reported, uncovering a paradox in which the MCO of depsipeptide monomers can produce “impossible” ring sizes: a 12-atom chain produced the expected 24-membered ring, alongside unexpected 18- and 30-membered cyclic oligomeric depsipeptides (CODs). We report an alternative preparation of authentic 18- and 36-membered macrocycles for this case using a stepwise synthesis that provides definitive analytical characterization for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…We prepared five non-natural ring-size congeners of ent -verticilide (24-membered COD), including 6-, 12-, 18-, 30-, and 36-membered CODs (Chart ). ent -Verticilide and the 18-membered COD were prepared using methodology previously reported. , The 6-, 12-, 30-, and 36-membered macrocycles were synthesized through a complementary route developed for this purpose (Scheme ). The synthesis of the depsipeptide unit begins with an enantioselective Henry reaction using hexanal ( 1 ) and nitromethane, followed by MOM protection of the subsequent alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…We prepared five non-natural ring-size congeners of ent -verticilide (24-membered COD), including 6-, 12-, 18-, 30-, and 36-membered CODs (Chart ). ent -Verticilide and the 18-membered COD were prepared using methodology previously reported. , The 6-, 12-, 30-, and 36-membered macrocycles were synthesized through a complementary route developed for this purpose (Scheme ). The synthesis of the depsipeptide unit begins with an enantioselective Henry reaction using hexanal ( 1 ) and nitromethane, followed by MOM protection of the subsequent alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in a study on macrocyclo-oligomerizations, it was observed that the tetradepsipeptide 13 underwent an intramolecular attack of the carboxylate at the central ester, leading to an anhydride isomer 14 , followed by fragmentation due to the nucleophilic attack of the alcoholic group and generation of the protected compound 15 and DKM 16 ( Scheme 3 ). 15 …”
Section: Solution-phase Synthesesmentioning
confidence: 99%
“…14 Recently, in a study on macrocyclo-oligomerizations, it was observed that the tetradepsipeptide 13 underwent an intramolecular attack of the carboxylate at the central ester, leading to an anhydride isomer 14, followed by fragmentation due to the nucleophilic attack of the alcoholic group and generation of the protected compound 15 and DKM 16 (Scheme 3). 15 Scheme 4 shows ester-based prodrugs (17) of glucagon-like peptide 1 (GLP) in its biologically active form GLP (7−36) and fused to peptide CEX, a nine-amino-acid C-terminal extension. 16 The N-terminal phenylalanine was replaced with phenyllactic acid, and the prodrugs dissociate under physiological conditions through formation of DKMs 1 and liberate the active peptide 18.…”
Section: Solution-phase Synthesesmentioning
confidence: 99%
“…Our original route to verticilide oligomers involved preparation of 1 by Mitsunobu-based oligomerization/macrocyclization . The permethylation step produced ent -verticilide in 78% yield. , This synthetic route afforded ent -verticilide concisely in six steps ( 7 → 6 → 1 , Scheme ).…”
mentioning
confidence: 99%
“…Instead of employing a traditional approach involving chain elongation through condensative couplings, the elongation steps and cyclization are accomplished in one step without protecting groups. This allows for a drastically reduced step count and rapid access to analogues …”
mentioning
confidence: 99%